Composition

JP7636459B2Active Publication Date: 2025-02-26NIPPON A & L INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023058903
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-31
Publication Date
2025-02-26
Estimated Expiration
2043-03-31

AI Technical Summary

Benefits of technology

【0005】 本発明によれば、耐水性に優れる組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636459000001
    Figure 0007636459000001
Patent Text Reader

Abstract

To provide a composition having excellent water resistance.SOLUTION: A composition comprises an aliphatic conjugated diene-based copolymer latex comprising a structural unit derived from a vinyl cyanide monomer of 33 mass% or more, and a crosslinker.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition. [Background technology]

[0002] Synthetic rubber latexes such as SBR, NBR, and MBR, and acrylic emulsions such as styrene-acrylic have been widely used in general paint compositions, paper coating compositions, and various adhesive compositions. In particular, NBR latex has excellent oil resistance of the polymer after drying, so it is widely used as a reinforcing agent for nonwoven fabrics, a raw material for rubber gloves, a raw material for foam rubber, a gasket material, etc., but in such applications, it may come into contact with tap water or industrial water, so water resistance in addition to oil resistance is also strongly required. Summary of the Invention [Problem to be solved by the invention]

[0003] However, the water resistance of the compositions has not yet been improved sufficiently by the conventional techniques. SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a composition having excellent water resistance. [Means for solving the problem]

[0004] The present invention provides the following: [1] A composition comprising an aliphatic conjugated diene copolymer latex containing 33 mass% or more of structural units derived from a vinyl cyanide monomer, and a crosslinking agent. [2] The composition according to [1], wherein the crosslinking agent contains a blocked isocyanate compound. [3] The composition described in [1] or [2], further comprising an emulsifier. [4] The composition described in claim [3], wherein the emulsifier contains an alkyl sulfosuccinate. Effect of the Invention

[0005] According to the present invention, a composition having excellent water resistance can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] The composition according to the present embodiment contains an aliphatic conjugated diene copolymer latex containing 33 mass % or more of structural units derived from a vinyl cyanide monomer, and a crosslinking agent.

[0007] The aliphatic conjugated diene copolymer latex has structural units derived from an aliphatic conjugated diene monomer, structural units derived from a vinyl cyanide monomer, and structural units derived from other copolymerizable monomers as required.

[0008] Examples of the aliphatic conjugated diene monomer include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted linear conjugated pentadiene, and substituted and side-chain conjugated hexadienes. These can be used alone or in combination of two or more. In this embodiment, it is preferable to use 1,3-butadiene from the viewpoints of industrial ease of production, availability, and cost.

[0009] Examples of vinyl cyanide monomers include acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, and α-ethylacrylonitrile. These may be used alone or in combination of two or more. In the present embodiment, it is preferable to use acrylonitrile or methacrylonitrile from the viewpoints of industrial ease of production, availability, and cost.

[0010] Examples of other copolymerizable monomers include ethylenically unsaturated carboxylic acid monomers, alkenyl aromatic monomers, unsaturated carboxylic acid alkyl ester monomers, unsaturated monomers containing a hydroxyalkyl group, unsaturated carboxylic acid amide monomers, etc. These monomers can be used alone or in combination of two or more.

[0011] Examples of the ethylenically unsaturated carboxylic acid monomer include monocarboxylic acid monomers such as acrylic acid, methacrylic acid, and crotonic acid, dicarboxylic acid monomers such as maleic acid, fumaric acid, and itaconic acid, and anhydrides thereof. These monomers can be used alone or in combination of two or more.

[0012] Examples of the alkenyl aromatic monomer include styrene, α-methylstyrene, methyl-α-methylstyrene, vinyltoluene, and divinylbenzene. These may be used alone or in combination of two or more. In this embodiment, it is preferable to use styrene from the viewpoints of industrial ease of production, availability, and cost.

[0013] Examples of the unsaturated carboxylic acid alkyl ester monomer include methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, glycidyl methacrylate, dimethyl fumarate, diethyl fumarate, dimethyl maleate, diethyl maleate, dimethyl itaconate, monomethyl fumarate, monoethyl fumarate, and 2-ethylhexyl acrylate. These can be used alone or in combination of two or more. In this embodiment, it is preferable to use methyl methacrylate from the viewpoints of industrial ease of production, availability, and cost.

[0014] Examples of unsaturated monomers containing a hydroxyalkyl group include β-hydroxyethyl acrylate, β-hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, 3-chloro-2-hydroxypropyl methacrylate, di-(ethylene glycol) maleate, di-(ethylene glycol) itaconate, 2-hydroxyethyl maleate, bis(2-hydroxyethyl) maleate, and 2-hydroxyethyl methyl fumarate. These can be used alone or in combination of two or more.

[0015] Examples of the unsaturated carboxylic acid amide monomer include acrylamide, methacrylamide, N-methylolacrylamide, N-methylolmethacrylamide, and N,N-dimethylacrylamide. These can be used alone or in combination of two or more.

[0016] In addition to the above monomers, monomers that are typically used in emulsion polymerization, such as ethylene, propylene, vinyl acetate, vinyl propionate, vinyl chloride, and vinylidene chloride, can also be used.

[0017] The content of structural units derived from an aliphatic conjugated diene monomer in the copolymer is preferably 45% by mass or more, more preferably 50% by mass or more, and even more preferably 55% by mass or more. Also, it is preferably 70% by mass or less, more preferably 65% ​​by mass or less, and even more preferably 60% by mass or less. By setting it in the above range, the balance of water resistance, dimensional stability, and anti-slip properties can be further improved.

[0018] The content of structural units derived from vinyl cyanide monomers in the copolymer is 33% by mass or more, preferably 34% by mass or more, and more preferably 35% by mass or more. Also, it is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less. By keeping it within the above range, it is possible to improve the balance between water resistance and anti-slip properties.

[0019] The aliphatic conjugated diene copolymer latex can be obtained, for example, by emulsion polymerization of the monomer components constituting the copolymer. In addition to the monomer components, the reaction system of the emulsion polymerization can contain an emulsifier (surfactant), a polymerization initiator, and, if necessary, a chain transfer agent, a reducing agent, etc. The method of adding the various components is not particularly limited, and any of a lump-sum addition method, a divided addition method, a continuous addition method, and a power feed method can be adopted. In addition, batch polymerization, semi-batch polymerization, seed polymerization, etc. can be used.

[0020] Examples of emulsifiers (surfactants) include anionic surfactants such as sulfate salts of higher alcohols, alkylbenzenesulfonates, alkyldiphenyletherdisulfonates, aliphatic sulfonates, aliphatic carboxylates, dehydroabietic acid salts, formalin condensates of naphthalenesulfonic acid, sulfate salts of nonionic surfactants, and nonionic surfactants such as alkyl esters, alkylphenyl ethers, and alkyl ethers of polyethylene glycols. These can be used alone or in combination of two or more.

[0021] Examples of chain transfer agents include alkyl mercaptans such as n-hexyl mercaptan, n-octyl mercaptan, t-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, and n-stearyl mercaptan; xanthogen compounds such as dimethyl xanthogen disulfide and diisopropyl xanthogen disulfide; thiuram compounds such as tetramethylthiuram disulfide, tetraethylthiuram disulfide, and tetramethylthiuram monosulfide; 2,6-di-t-butyl-4-methylphenol, Examples of the chain transfer agents include phenolic compounds such as ethyleneated phenol; allyl compounds such as allyl alcohol; halogenated hydrocarbon compounds such as dichloromethane, dibromomethane, and carbon tetrabromide; vinyl ethers such as α-benzyloxystyrene, α-benzyloxyacrylonitrile, and α-benzyloxyacrylamide; and chain transfer agents such as triphenylethane, pentaphenylethane, acrolein, methacrolein, thioglycolic acid, thiomalic acid, 2-ethylhexylthioglycolate, terpinolene, and α-methylstyrene dimer. These can be used alone or in combination of two or more. The amount of the chain transfer agent can be appropriately adjusted in consideration of the combination with other additives.

[0022] In addition, for the purpose of controlling the molecular weight and crosslinking structure of the copolymer, it is possible to blend hydrocarbon compounds such as saturated hydrocarbons such as pentane, hexane, heptane, octane, cyclohexane, and cycloheptane; unsaturated hydrocarbons such as pentene, hexene, heptene, cyclopentene, cyclohexene, cycloheptene, 4-methylcyclohexene, and 1-methylcyclohexene; and aromatic hydrocarbons such as benzene, toluene, and xylene. These can be used alone or in combination of two or more. Of these, it is preferable to use cyclohexene and toluene.

[0023] Furthermore, if necessary, the reaction system may contain additives such as electrolytes, oxygen scavengers, chelating agents, dispersants, defoamers, antioxidants, preservatives, antibacterial agents, flame retardants, ultraviolet absorbing agents, etc. These additives may be used in appropriate amounts and of appropriate types.

[0024] The toluene insoluble content of the aliphatic conjugated diene copolymer latex is preferably 100% by mass or less, more preferably 95% by mass or less, and even more preferably 90% by mass or less. Also, it is preferably 60% by mass or more, more preferably 70% by mass or more, and preferably 80% by mass or more. By setting it in the above range, the balance of water resistance, dimensional stability, and anti-slip properties can be further improved. For example, the toluene insoluble content can be adjusted by changing the amount of the chain transfer agent. The toluene insoluble content can be measured by the method described in the Examples.

[0025] The glass transition temperature (Tg) of the aliphatic conjugated diene copolymer latex is preferably -35°C or higher, more preferably -30°C or higher, and even more preferably -25°C or higher. It is also preferably 15°C or lower, more preferably 0°C or lower, and even more preferably -15°C or lower. By setting it within the above range, the balance of water resistance, dimensional stability, and anti-slip properties can be further improved. The glass transition temperature can be measured by the method described in the Examples.

[0026] Furthermore, if necessary, the aliphatic conjugated diene copolymer latex may be blended with functional additives such as dispersants, preservatives, antiaging agents, printability improvers, surfactants, viscosity modifiers, etc. These additives may be used in appropriate amounts in terms of type and amount.

[0027] Examples of the crosslinking agent include epoxy compounds, melamine resins, ethylene urea compounds, blocked isocyanate compounds, ethyleneimines, carbodiimides, oxazoline compounds, alkoxysilane compounds, zirconium salt compounds, zinc oxide, urea resins, sulfur, and peroxides. These can be used alone or in combination of two or more. It is preferable to use epoxy compounds, blocked isocyanate compounds, zinc oxide, sulfur, and urea resins, and it is more preferable to use blocked isocyanate compounds, since they can further improve the balance of water resistance, dimensional stability, and stability over time.

[0028] The content of the crosslinking agent is preferably 1 part by mass (solid content) or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by weight (solid content) of the aliphatic conjugated diene copolymer latex. Also, it is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less. By setting it in the above range, water resistance can be improved.

[0029] The composition preferably further contains an emulsifier, and examples of the emulsifier include the same emulsifiers as those exemplified as emulsifiers that can be used in emulsion polymerization of aliphatic conjugated diene copolymer latex. These can be used alone or in combination of two or more. Since it can further improve froth formability, it is preferable to use an anionic surfactant, more preferably to use a sulfonate-based anionic surfactant, and even more preferably to use an alkyl sulfosuccinate.

[0030] The content of the emulsifier is preferably 1 part by mass (solid content) or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by weight (solid content) of the aliphatic conjugated diene copolymer latex. Also, it is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less. By setting it in the above range, the froth formability can be further improved.

[0031] Furthermore, if necessary, known additives such as antiaging agents, ultraviolet absorbers, flame retardants, preservatives, antibacterial agents, deodorants, pH adjusters, thickeners, penetrants, foaming agents, defoamers, coloring pigments, and fragrances may be added to the composition. In addition, polyorganosiloxanes and starches having a blister prevention function may be added. These additives can be used in appropriate amounts in terms of type and amount.

[0032] The composition according to the present embodiment is excellent in water resistance as well as oil resistance, and is therefore useful in applications where these properties are particularly required, such as those described in the Background Art. It is also useful for other applications, such as paper coating, fiber bonding for nonwoven fabrics, carpet backing, batteries (e.g., electrodes, separators, heat-resistant protective layers, etc.), paints, and adhesives.

[0033] When applying, impregnating, or adhering the composition according to the present embodiment, a conventionally known device or method can be used, and the composition can be foamed or thickened before use. When drying, a conventionally known device or method can be used. EXAMPLES

[0034] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples. Furthermore, unless otherwise specified, % and parts are based on mass.

[0035] <Measurement of toluene insoluble matter of aliphatic conjugated diene copolymer latex> A copolymer latex film is made by drying for 5 hours in an atmosphere at a temperature of 85°C. Approximately 1 g of the latex film is then weighed out and designated as Xg. This is then placed in 400 ml of toluene and allowed to swell and dissolve for 48 hours. This is then filtered through a weighed 300 mesh stainless steel mesh, after which the toluene is evaporated to dryness, and the weight of the mesh is subtracted from the dried weight to determine the dried weight of the sample, which is then weighed and designated as Yg. Insoluble in toluene (mass%) = Y / X x 100

[0036] <Measurement of glass transition temperature (Tg) of aliphatic conjugated diene copolymer latex> The copolymer latex is cast onto a glass plate and dried at 70°C for 4 hours to produce a film, which is then packed into an aluminum pan and set into a differential scanning calorimeter (DSC6200: Seiko Instruments Inc.). The apparatus is cooled in advance to a temperature about 50°C lower than the expected Tg, and then the temperature is increased at a heating rate of 10°C / min to plot a DSC curve.

[0037] In the present invention, the glass transition temperature refers to, in a differential curve of a DSC measurement chart, (a) the temperature at the top of the peak when there is one peak, (b) the temperature at the top of the peak with the largest area when there are two or more peaks, (c) the temperature at the top of the peak when there is a peak top but the shape is broad, (d) the temperature at the center of a broad (trapezoidal) peak when there is no peak top, or (e) the temperature obtained based on the criteria (c) or (d) when there are two or more peaks and the shape of the part with the largest area falls under (c) or (d), respectively.

[0038] <Aliphatic conjugated diene copolymer latex> A-1: High nitrile type (acrylonitrile content: 36 to 42% by mass) Modified NBR (NA-25 manufactured by Nippon A&L Co., Ltd.) Insoluble in toluene: 85% by mass, glass transition temperature: -20°C A-2: Medium nitrile type (acrylonitrile content: 25-30% by mass) Modified NBR (NA-106 manufactured by Nippon A&L Co., Ltd.) Insoluble in toluene: 45% by mass, glass transition temperature: -35°C

[0039] <Crosslinking agent> B-1: Blocked isocyanate compound (XC-910, manufactured by Aica Kogyo Co., Ltd.) B-2: Epoxy compound (Denacol EX521, manufactured by Nagase ChemteX Corporation) B-3: A mixture of sulfur / zinc oxide / urea = 1 / 1.5 / 0.6 (mass ratio)

[0040] <Preparation of Composition> According to the formulation shown in Table 1, 100 parts by weight of aliphatic conjugated diene copolymer latex, 5 parts by weight of crosslinking agent, 6 parts by weight of N-tallow alkyl sulfosuccinamate (Lipearl NTD manufactured by Lion Corporation) as an emulsifier, and 50 parts by weight of aluminum hydroxide as an inorganic filler were mixed, and the solid content was adjusted to 55% using a specified amount of thickener and water to obtain composition A. Moreover, compositions B to E were obtained in the same manner as composition A, except that the formulation was changed to that shown in Table 1.

[0041] <Water resistance evaluation> Each composition was applied uniformly to a glass plate with a clearance of 2 mm, and dried for 24 hours at a temperature of 23°C and a humidity of 50%. The resulting film was cut into 3cm x 3cm pieces, and the water absorption rate was measured from the weight of the film before and after immersion in tap water for 24, 48, and 72 hours. The evaluation results were rated on a four-point scale: A, B, C, and D. The results are shown in Table 1. (Excellent) A > B > C > D (Poor)

[0042] <Evaluation of dimensional stability> Each composition was applied uniformly to a glass plate with a clearance of 2 mm, and dried for 24 hours at a temperature of 23°C and a humidity of 50%. A 5cm x 5cm square was printed on the resulting film, and the film was immersed in tap water for 24, 48, and 72 hours, after which the rate of change in the size of the square was measured. The results were rated on a four-point scale: A, B, C, and D. The results are shown in Table 1. (Excellent) A > B > C > D (Poor)

[0043] <Evaluation of anti-slip properties> Each composition was foamed twice as much using a hand mixer, and applied to a cotton cloth with a coating bar with a clearance of 2 mm, and then dried for 30 minutes in a dryer set at 130°C. The foam obtained was placed face down on a Teflon (registered trademark) plate and the anti-slip properties were evaluated sensorily. The evaluation results were rated on a four-point scale of A, B, C, and D. The results are shown in Table 1. (Excellent) A > B > C > D (Poor)

[0044] [Table 1]

Claims

[Claim 1] A foaming composition comprising an aliphatic conjugated diene copolymer latex containing 33 mass% or more of structural units derived from a vinyl cyanide monomer, and a crosslinking agent, the crosslinking agent containing a blocked isocyanate compound, and further containing an emulsifier containing an alkyl sulfosuccinate.

Citation Information

Patent Citations

  • Treatment of polyester fiber for rubber reinforcement

    JP1990251680A

  • Polyester fiber for composite material with chlorosulfonated polyethylene and chloroprene-acrylic rubber

    JP1991167372A

  • Glass fiber treating agent for rubber reinforcement, rubber reinforcing cord using the same and rubber product

    JP2003268678A

  • Method for producing nitrile rubber, nitrile rubber produced therefrom, and rubber composition containing said rubber

    JP2022516938A

  • Glove

    WO2017126660A1